Transforming Norton: Thomas Norton and the Impact of Geneva - Duguid, Timothy (Reformation & Renaissance review, 2024)
The Geneva Bible (1560) is well known to have influenced Protestant culture in Elizabethan England, as its texts have been detected in the literary works of some of the finest writers of the period. Still, the timing and circumstances of the translation’s ascendancy in the English consciousness remain murky. This article uses the metrical psalms written by Elizabethan politician and lawyer Thomas Norton in 1560–1562 as a case study of the early impact of the Geneva Bible. Its source analysis of Norton’s psalm versifications traces the immediate influence of the Geneva Bible on this man as he contributed to one of the most popular and long-lasting editions of anglophone psalmody: the Sternhold and Hopkins metrical psalms, which would continue to be printed well into the nineteenth century.